Improving SEP for Heterogeneous Wireless Sensor Networks - Al-Mejibli, Intisar SH. (Iraqi Journal of Science, 2024)
The lifespan of WSNs is crucial, and it primarily relies on the energy efficiency of the sensors, as their power source is often non-rechargeable and non-replaceable batteries. Addressing this issue involves carefully designing of a routing protocol that considers energy saving. This article presents a heterogeneity-aware routing protocol based on the Stable Election Protocol SEP for heterogeneous WSNs to extend the lifespan of the WSN by reducing energy consumption. The proposal employs the Time Difference of Arrival (TDoA) in the cluster-forming process to determine the shortest distance between the cluster head (CH) and sensor nodes in that cluster, thereby minimizing power consumption in all later communication operations. The proposal has been evaluated and compared to three protocols which are SEP, Zonal-SEP (Z-SEP), and Improved Z-SEP (IZ-SEP). The results depicts that the proposed protocol outperforms the three protocols in terms of the largest number of alive nodes in all evaluation rounds and exhibited a greater average of residential energy in nodes by about 90%, 10%, and 5% more than SEP, Z-SEP, and IZ-SEP respectively.